Towards a high-performance HR bundle process for lean service operations - Zirar, Araz; Trusson, Clive; Choudhary, Alok (The International journal of quality & reliability management, 2021)
PurposeThis article presents an empirically induced “high-performance” “human resources (HR) bundle”, comprising six HR practices, for supporting lean service operations.Design/methodology/approachThis was a multiple case study. A qualitative data set, including transcripts from 27 semistructured in-depth interviews with lean practitioners from across five service organizations that have adopted lean practices, was thematically analyzed to establish key HR practices on the road to lean maturity.FindingsA “high-performance” HR bundle of three work practices and three employment practices emerged from the analysis. These practices typically mature implicitly rather than systematically to support organizations in successfully implementing lean service operations by resourcing the most suitable people for carefully defined roles, providing workers with extensive lean training opportunities, appraising workers' performances such that lean behaviours are recognized and rewarded and encouraging a participative teamworking culture.Research limitations/implicationsThis article uses cross-sectional data from five case studies to induce a “high-performance” “HR bundle” theoretical model and process. A larger number of case studies and/or longitudinal data would add credence.Practical implicationsLean service managers should regard HR practices as integral to the lean maturation process and might usefully conceive of them as processes allowing for greater management control to achieve incremental improvements to lean service provision.Originality/valueThe article provides deeper understanding of the importance of HR practice for lean service organizations and offers practical suggestions for managing HR practices in this context.